(untitled) (Global Journal of Science Frontier Research, 2018)
The present study aimed to assess the effect of water pollution on physiological and histological alterations of African catfish, Clarias gariepinus collected from spring 2015 to winter 2016, in two differingquality aquatic ecosystems in Nile Delta, Egypt, namely Damietta Branch of River Nile and Ammar Drain. Results showed significant differences (p≤0.001) in all estimated physicochemical environmental factors in study areas. In addition, the results showed that the bad water quality in Ammar Drain due to pollution, the vast majority of the hematological parameters recorded lower levels in Ammar Drain than in River Nile. Because Ammar Drain receives greater agricultural, industrial and domestic wastes than the second one. Antioxidant enzyme activities were lower in fish from the contaminated site compared with fish from the reference site, suggesting a deficiency of the antioxidant system to overcome the oxidative stress. Lesions of histological deformations (skin, muscles, and gonads) were detected and analyzed to clarify the effect of water pollution on fish organs. The present study recommended treatment of the waste before being discharged into the waterways.